Ranolazine Prevents Phenotype Development in a Mouse Model of Hypertrophic Cardiomyopathy. (March 2017) - Coppini, Raffaele; Mazzoni, Luca; Ferrantini, Cecilia; Gentile, Francesca; Pioner, Josè Manuel; Laurino, Tina; Santini, Lorenzo; Bargelli, Valentina; Rotellini, Matteo; Bartolucci, Gianluca; Crocini, Claudia; Sacconi, Leonardo; et al.
Abstract : Background—: Current therapies are ineffective in preventing the development of cardiac phenotype in young carriers of mutations associated with hypertrophic cardiomyopathy (HCM). Ranolazine, a late Na + current blocker, reduced the electromechanical dysfunction of human HCM myocardium in vitro. Methods and Results—: To test whether long-term treatment prevents cardiomyopathy in vivo, transgenic mice harboring the R92Q troponin-T mutation and wild-type littermates received an oral lifelong treatment with ranolazine and were compared with age-matched vehicle-treated animals. In 12-months-old male R92Q mice, ranolazine at therapeutic plasma concentrations prevented the development of HCM-related cardiac phenotype, including thickening of the interventricular septum, left ventricular volume reduction, left ventricular hypercontractility, diastolic dysfunction, left-atrial enlargement and left ventricular fibrosis, as evaluated in vivo using echocardiography and magnetic resonance. Left ventricular cardiomyocytes from vehicle-treated R92Q mice showed marked excitation–contraction coupling abnormalities, including increased diastolic [Ca 2+ ] and Ca 2+ waves, whereas cells from treated mutants were undistinguishable from those from wild-type mice. Intact trabeculae from vehicle-treated mutants displayed inotropic insufficiency, increased diastolic tension, and premature contractions; ranolazine treatment counteracted the development of myocardial mechanical abnormalities. In mutant myocytes, ranolazine inhibited the enhanced late Na + current and reduced intracellular [Na + ] and diastolic [Ca 2+ ], ultimately preventing the pathological increase of calmodulin kinase activity in treated mice. Conclusions—: Owing to the sustained reduction of intracellular Ca 2+ and calmodulin kinase activity, ranolazine prevented the development of morphological and functional cardiac phenotype in mice carrying a clinically relevant HCM-related mutation. Pharmacological inhibitors of late Na + current are promising candidates for an early preventive therapy in young phenotype-negative subjects carrying high-risk HCM-related mutations. Abstract : Supplemental Digital Content is available in the text.